Regulating Hosting ISPs' Responsibilities for Copyright Infringement The Freedom to Operate in the US, EU and China - Wang, Jie (Springer Singapore, 2018)
This book employs a comparative approach to comprehensively discuss hosting ISPs' responsibilities for copyright infringement in the US, EU and China. In particular, it details how the current responsibility rules should be interpreted or revised so as to provide hosting ISPs maximum freedom to operate in these jurisdictions. In addition to examining relevant state regulations, the book assesses self-regulation norms agreed upon between copyright owners and hosting ISPs, and concludes that self-regulation is better suited to preserving hosting ISPs' freedom to operate. The results of this study will be interesting for a broad readership, including academics and practitioners whose work involves hosting ISPs' copyright responsibilities.